Rééduquer des « mauvaises filles » et des « mauvais garçons » : deux foyers pour mineurs délinquants en Guadeloupe, Saint-Jean Bosco et Notre-Dame de Grâce (1935-1970) - Claire Palmiste (Amnis)
This paper purports to examine the stakes of setting up a rehabilitation scheme for delinquent girls and boys in Guadeloupe by two denominational institutions in a context of changes in Guadeloupe. It also aims at understanding the articulation between the traditional categories of race, gender and class in juvenile delinquency and the way it was handled.